2015 IEEE 27th International Symposium on Power Semiconductor Devices &Amp; IC's (ISPSD) 2015
DOI: 10.1109/ispsd.2015.7123470
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of temperature humidity bias (THB) testing on IGBT modules by high bias levels

Abstract: The temperature-humidity-bias (THB) test is the standard for accelerated stress testing with respect to corrosion and other humidity driven degradation mechanisms. Usually, 1000 hrs tests at 85 degree Celsius and 85 percent relative humidity (85/85) are used to predict up to 25 years of operation. With regard to the respective standards asking for limited selfheating, the bias was commonly limited to 80 V. Nevertheless, recent THB tests on 1.7 kV IGBT modules have shown that higher bias is a more severe test c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…Moisture can lead to corrosion of the aluminum inside the module and, hence, faults. Zorn and Kaminski [127] showed that the increase of moisture causes a decrease of avalanche voltage and, above a certain level of humidity, a surge in the leakage current. This leads to temperature stress, especially at the junction the IGBT.…”
Section: Converter Reliabilitymentioning
confidence: 99%
“…Moisture can lead to corrosion of the aluminum inside the module and, hence, faults. Zorn and Kaminski [127] showed that the increase of moisture causes a decrease of avalanche voltage and, above a certain level of humidity, a surge in the leakage current. This leads to temperature stress, especially at the junction the IGBT.…”
Section: Converter Reliabilitymentioning
confidence: 99%
“…The levels of humidity in the environment can impact the embedded system. High levels of humidity can lead to condensation of water onto circuits, which can result in corrosion of components (Zorn & Kaminski, 2014).…”
Section: Environmentalmentioning
confidence: 99%
“…The collector current instead changes almost continuously, as it is directly related to the power generated by the wind turbine. The values of the switching parameters can be captured by measuring the instantaneous collector current I C , the collector-emitter voltage V CE and the gate-emitter voltage V GE and then applying the definition of t on , t don , t off and t doff [10]:  turn-on delay time: time from 10% of the gate voltage to 10% of collector current;  turn-on time: time from 10% of the gate voltage to 90% of collector current;  turn-off delay time: time from 90% of the gate voltage to 10% of the collector voltage;  turn-off time: time from 90% of the gate voltage to 10% of the collector current. Fig.…”
Section: Sensitivity Analysis Of Switching Parametersmentioning
confidence: 99%
“…On the other hand, a small initial crack in the die-attached solder generated during the manufacturing process can be aggravated by small and short temperature swings leading to full SF. The root causes of solder failures are temperature changes and mean humidity [10].…”
Section: Introductionmentioning
confidence: 99%